2015
DOI: 10.1136/bjophthalmol-2015-306885
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factor analysis of vitrectomy for myopic foveoschisis

Abstract: Eyes with myopic foveoschisis with preoperative ellipsoid disruption and thinner central foveal thickness tend to have poorer visual outcomes. While current surgical manoeuvres are effective in reattaching the fovea, they may also cause iatrogenic injury to the photoreceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
0
10
0
8
Order By: Relevance
“…Intraoperative gas tamponade itself could contribute to a better prognosis, but compared with other factors, the effect on visual outcome was relatively small. Several articles estimating prognostic factors have recently been published [11,12,23]. Lim et al [12] demonstrated that preoperative ellipsoid disruption and thinner CFT were related to poor prognosis after PPV in MF patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative gas tamponade itself could contribute to a better prognosis, but compared with other factors, the effect on visual outcome was relatively small. Several articles estimating prognostic factors have recently been published [11,12,23]. Lim et al [12] demonstrated that preoperative ellipsoid disruption and thinner CFT were related to poor prognosis after PPV in MF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative visual acuity [11] and various OCT findings, as well as operative techniques, have been identified as prognostic factors in this respect. For example, preoperative ellipsoid disruption and thinner central foveal thickness (CFT) are known to be useful OCT findings [12]. However, the usefulness of gas tamponade or ILM peeling remains controversial [13][14][15], and the role of additional factors remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Lappen der Limitans-interna-Membran zur Behandlung von großen Makulalöchern: anatomische und funktionelle Kurzzeitergebnisse Background A macular hole (MH) is a full-thickness neuroretinal defect of the fovea causing a reduction in central vision. Although anatomical success following primary pars plana vitrectomy (PPV) and internal limiting membrane peel (ILM) with gas tamponade have improved to 60-100 %, closure rates are significantly lower in large MH (> 400 µm), atrophic MH and MH associated with high myopia [1,2]. In 2010, Michalewska et al described a technique for the primary repair of large MHs, where a remnant of an incompletely peeled ILM was used to cover the base of the hole [3].…”
Section: Internal Limiting Membrane Flap Techniques For the Repair Ofmentioning
confidence: 99%
“…Einführung Das Makulaloch (ML) ist ein Netzhautdefekt der Fovea, welcher das zentrale Sehen beeinträchtigt. Obwohl in 60-100 % der Fälle ein anatomischer Verschluss nach primärer Pars-plana-Vitrektomie (PPV) mit Membrana-limitans-interna-Peeling (ILM-Peeling) und Gasendotamponade erzielt wird, sind die Verschlussraten bei größeren ML (> 400 µm), atrophen ML sowie ML bei hoher Myopie tendenziell geringer [1,2]. Im Jahr 2010 haben Michalewska et al eine neue Technik für die Erstbehandlung von großen ML vorgestellt.…”
Section: Long-term Outcome After Autologous Free Internal Limiting Meunclassified